KEKUATAN HUKUM TANDA TANGAN DIGITAL DALAM PEMBUKTIAN SENGKETA PERDATA MENURUT UNDANG-UNDANG NOMOR 11 TAHUN 2008 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK - I Kadek Wista Juana (Fakultas Hukum Universitas Dwijendra, 2019)
Abstract A digital signature is a signature that is made electronically which functions the same as a normal signature on an ordinary paper document. A signature is data which if not falsified can function to justify the actions of the person whose name is written on the document signed by him. Digital signatures can actually guarantee documents security compared to ordinary signatures. Electronic message recipients with digital signatures can check whether the message actually came from the correct sender and whether the message has been changed after being signed either intentionally or unintentionally in the case of an electronic payment system, other evidence that can be used other than electronic data or digital in the form of digital signatures to be classified. The formulation of this research problem is how the authenticity of digital signatures according to Law Number 11 of 2008 concerning Information and Electronic Transactions and how the power of digital signature law in proving civil disputes are reviewed from Law Number 11 Year 2008 concerning Information and Electronic Transactions.The research method used in the preparation of this study is a type of normative research. According to Peter Mahmud Marzuki, Research on normative law is a process of finding legal rules, legal principles and legal doctrines in order to answer the legal issues at hand.The results of the discussion in this study are as follows: It needs to be well understood by legal practitioners that an electronic signature, not a scanned signature, is then placed on a document, so that a document is indeed impressed (on a computer monitor) signed. The definition of actual electronic signatures (according to the ITE Law) can be made in various ways including a digital code affixed to a message that is sent electronically, which will specifically provide a specific identification from the sender. The strength of evidentiary forces inherent in digital signatures viewed from proof of civil procedural law has the strength of the evidence load at the level of the lower hand deed (ABT), therefore the burden of evidence attached to the electronic mail is only the strength of formal proof and material proof. Keywords : Proof, Digital Signature, Civil Law.